2015
DOI: 10.1016/j.omega.2015.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Using data envelopment analysis for the assessment of technical efficiency of units with different specialisations: An application to agriculture

Abstract: Citation: ATICI, K.B. and PODINOVSKI, V.V., 2015. Using data envelopment analysis for the assessment of technical efficiency of units with different specialisations: an application to agriculture. Omega, 54, Additional Information:• This paper was accepted for publication in the journal AbstractIn this paper we consider the use of data envelopment analysis (DEA) for the assessment of efficiency of units whose output profiles exhibit specialisation. An example of this is found in agriculture where a large numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…In the process of agricultural production, input means agricultural production and produce products (or value), while waste and emissions (or other undesirable outputs) are unavoidable [25,40]. Therefore, this research, according to the eco-efficiency evaluation criteria of the WBCSD, refers to some of the latest research on the eco-efficiency evaluation [40][41][42][43][44], combined with the availability of data, to construct evaluation index system.…”
Section: Data Selection and Dmumentioning
confidence: 99%
“…In the process of agricultural production, input means agricultural production and produce products (or value), while waste and emissions (or other undesirable outputs) are unavoidable [25,40]. Therefore, this research, according to the eco-efficiency evaluation criteria of the WBCSD, refers to some of the latest research on the eco-efficiency evaluation [40][41][42][43][44], combined with the availability of data, to construct evaluation index system.…”
Section: Data Selection and Dmumentioning
confidence: 99%
“…DEA is widely applied to efficiency measurement of decision making units (DMUs) in various industries, including agriculture [6,7], industry [8,9] and service industry-such as finance [10,11], education [12,13], retail [14,15], healthcare service and so on. Thereby, in the field of healthcare service, the applications of DEA method mainly focus on the simple efficiency measurement of medical and healthcare institutions or organizations.…”
Section: Introductionmentioning
confidence: 99%
“…According to t he latest OECD policy classification criteria (OECD 2009) and the research conducted (Zong and Li 2006;Gao and He 2010;Galanopoulos et al 2011;Atici and Podinovski 2015;Liu et al 2015), the indicator system which this paper set up is as shown in Table 2. Overall, this paper use six inputs (PSE, GSSE, labour, sown-area, machinery, fertilizer) in our DEA models.…”
Section: Indicator Selectionmentioning
confidence: 99%